2021
DOI: 10.2987/21-7012
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory and Greenhouse Performance of Five Commercial Light Traps for Capturing Mosquitoes in China

Abstract: Mosquito light traps for household use are popular because they are small, cheap, user friendly, and environment friendly. At present, there are many variations and specifications of mosquito traps intended for household use on the market. The light traps claim they are powerful, but research and evaluation are lacking. Key parameters such as capture rates in the laboratory and field of 5 popular mosquito traps were evaluated as intended for household use. This study found that in the laboratory experiments, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
(18 reference statements)
1
1
0
Order By: Relevance
“…This study thus showed that the use of the "Electron go out mosquito small lamp" induces an average decrease of about 55.4% of culicidal density in the human habitation structure of its use. Confirming the results of work done in 2021 by Huang, Run et al [12] on the effectiveness of light traps for the capture of mosquitoes which had shown by the method of capture and recapture in the laboratory that such devices have a success rate between 34.7% and 65%. This study also demonstrates the attractive capacity of blue UV light whose wavelength is around 400 nm, confirming the attraction of mosquitoes to blue and green light [13].…”
Section: Discussionsupporting
confidence: 75%
“…This study thus showed that the use of the "Electron go out mosquito small lamp" induces an average decrease of about 55.4% of culicidal density in the human habitation structure of its use. Confirming the results of work done in 2021 by Huang, Run et al [12] on the effectiveness of light traps for the capture of mosquitoes which had shown by the method of capture and recapture in the laboratory that such devices have a success rate between 34.7% and 65%. This study also demonstrates the attractive capacity of blue UV light whose wavelength is around 400 nm, confirming the attraction of mosquitoes to blue and green light [13].…”
Section: Discussionsupporting
confidence: 75%
“…While previous studies reported behavioral attraction to ultraviolet (UV) light for Aedes, Anopheles, and Culex in semi-field setting and in field conditions at night [24,25], we extended our Y-maze assay to study mosquito photobehavior to UV light versus darkness (Fig. 1g).…”
Section: Adult Female Mosquitoes Are Photonegativementioning
confidence: 99%